The essence of law enforcement activity - Tabaka, Taras (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article examines the problems of the essence of law enforcement activity in the conditions of war in Ukraine, reveals various views of scientists on the definition of the studied concept. The author highlights the following main features of law enforcement activity: aimed at protecting the rights, rights, freedoms and legitimate interests of a person and ensuring law and order; implemented on the basis of the law with the help of legal measures provided for by law; are carried out by special state bodies or subjects authorized by the state (public formations, organizations, officials). The author divides law enforcement activities into the following types: protection of the order of social relations established by law - fight against offenders; public safety activities; fight against crime - disclosure and investigation of crimes; supervision of compliance with legislation; ensuring the execution of decisions of courts and other bodies in cases provided for by law; ensuring state policy in the field of justice; provision of qualified legal assistance to citizens and organizations, notarial activities, activities of private security and detective firms, etc. The structure of law enforcement agencies is considered. The article notes the researchers’ opinion that law enforcement agencies cannot be demanded to eradicate and reduce crime. Their activities are only one of the factors that neutralize many aspects of crime. According to the author, public opinion is one of the main criteria for the official evaluation of the activities of law enforcement agencies, and in particular the Military Law and Order Service in the Armed Forces of Ukraine. It is determined by public trust and citizen support for the activities of law enforcement agencies. Therefore, in order to increase public trust and support their activities, law enforcement agencies should more actively involve citizens and public associations in law enforcement activities. On the basis of the conducted legal analysis, reasonable conclusions were made.